Place of death in the population dying from diseases indicative of palliative care need: a cross-national population-level study in 14 countries - Pivodic, Lara; Pardon, Koen; Morin, Lucas; Addington-Hall, Julia; Miccinesi, Guido; Cardenas-Turanzas, Marylou; Onwuteaka-Philipsen, Bregje; Naylor, Wayne; Ruiz Ramos, Miguel; Van den Block, Lieve; Wilson, Donna M; Loucka, Martin; et al. (Journal of epidemiology and community health, 2016)
BACKGROUND: Studying where people die across countries can serve as an evidence base for health policy on end-of-life care. This study describes the place of death of people who died from diseases indicative of palliative care need in 14 countries, the association of place of death with cause of death, sociodemographic and healthcare availability characteristics in each country and the extent to which these characteristics explain country differences in the place of death. METHODS: Death certificate data for all deaths in 2008 (age ≥1 year) in Belgium, Canada, the Czech Republic, England, France, Hungary, Italy, Mexico, the Netherlands, New Zealand, South Korea, Spain (Andalusia), the USA and Wales caused by cancer, heart/renal/liver failure, chronic obstructive pulmonary disease, diseases of the nervous system or HIV/AIDS were linked with national or regional healthcare statistics (N=2,220,997). RESULTS: 13% (Canada) to 53% (Mexico) of people died at home and 25% (the Netherlands) to 85% (South Korea) died in hospital. The strength and direction of associations between home death and cause of death, sociodemographic and healthcare availability factors differed between countries. Differences between countries in home versus hospital death were only partly explained by differences in these factors. CONCLUSIONS: The large differences between countries in and beyond Europe in the place of death of people in potential need of palliative care are not entirely attributable to sociodemographic characteristics, cause of death or availability of healthcare resources, which suggests that countries' palliative and end-of-life care policies may influence where people die.
Keywords: Infant; Humans; kojenec; lidé středního věku; PALLIATIVE CARE; Palliative Care; dítě; Child; Female; Aged; mladý dospělý; dospělí; úmrtní listy; internacionalita; Internationality; Health Services Needs and Demand; Residence Characteristics; Terminally Ill; senioři; lidé; Death Certificates; smrt; předškolní dítě; Adult; charakteristiky bydlení; umírající; ženské pohlaví; Male; Middle Aged; PUBLIC HEALTH; Adolescent; paliativní péče; Aged, 80 and over; Cause of Death; Young Adult; senioři nad 80 let; příčina smrti; CHRONIC DI; Death; mužské pohlaví; DEATH CERTIFICATION; zdravotnické služby - potřeby a požadavky; Child, Preschool; mladiství